(untitled) (REMUNOM, 2026)
This study aimed to evaluate the influence of storage temperature on the physicochemical stability, bioactive compounds, and antioxidant capacity of mixed biquinho pepper and yellow passion fruit jams with added honey. Mixed jams were formulated and subjected to microbiological, physicochemical, bioactive compound, and antioxidant capacity analyses using a completely randomized design. Samples were stored at three temperatures (25, 35, and 45 °C) and analyzed over 90 days. Data were subjected to analysis of variance and mean testing (Scott-Knott) at a 5% significance level. Microbiological results indicated growth of filamentous fungi and yeasts in samples stored at 25 °C and 35 °C after 30 days, whereas no microbial growth was observed at 45 °C, suggesting that higher temperatures inhibit these microorganisms. Physicochemical analyses revealed that moisture was the parameter most sensitive to increased temperature, showing a significant reduction and syneresis at the end of storage at 45 °C. Elevated temperatures also reduced C* values, resulting in a more opaque appearance of the jams. Furthermore, bioactive compounds and antioxidant capacity increased, influenced by storage temperature, formulation ingredients, and the addition of honey.